Efeitos ecadeados do perfil setorial dos investimentos e a distribuiç\~ao espacial da indústria: Onde se localizam as indústrias dos setores com maiores impactos? - Bruno de Oliveira Cruz; Iuri Vladimir Queiroz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– In a recent report, BNDES, a major bank financing investment in Brazil, announced that investment in some selected sector for the period 2014-2017 could reach the impressive US 275 billion. Oil and Gas, vehicle and automobile, pulp and paper, electronics, chemistry, Steel mill are among the sector which would expand activities in the next four years. In a very important paper, Ellison, Glaeser and Kerr (2010) showed that input-output linkages are the most important variable to explain industries co-agglomeration. Those investments perspectives open a new possibility for regional policies, following the results of EGK, one could estimate the backward and forward linkages and possibility to co-agglomerate industries, given the potential investment in the sectors described above. The objective of this paper is to identify the backward and forward linkages of the investment matrix for the period 2014 and estimate the spatialdistribution of those sectors in backward and forward linkages with the original initial investment. In other words, we apply the co-agglomerations indexes to asses which sector has the highest probability, given an investment in a sector, for instance Oil and Gas and backward/forward linkage, the co-agglomerate. The identification of those sectors can shed some lights on sectors policy makers could successfully support and can improve the performance of the regional policies.
Keywords: R12; C67; 330; input-output matrix; co-aglomeration; investment